Predicate Decomposition, and Linking Syntax and Semantics: A Brazilian Portuguese Analysis - Cançado, Márcia; Godoy, Luisa (Linguistik Online, 2014)
This paper presents a theoretical proposal on the lexical-syntax relationship, related to verbs. In essence, the proposal consists of two tasks: a) to corroborate the idea of lexically representing verbs by means of a semantic predicate decomposition and, more importantly, b) to propose a linking mechanism between such lexical-semantic level and syntax itself. The contribution of this study consists in the form and manner in which the linking occurs. Even though linking theories abound in the literature, and even though in a general sense the approach presented here is not new, there are some relevant details that distinguish it from previous proposals, as it will become clear. Furthermore, from an empirical point of view, there is originality in the description we make of a vast group of verbs from Brazilian Portuguese (BP) that serves as a demonstration of the theoretical proposal.